Identifikasi Karakteristik Accumulator Menggunakan Citra Termal Berbasis Pengolahan Citra - Sri Ratna Sulistiyanti; F.X. Arinto Setyawan; Tiya Muthia; Yudi Eka Putra (Department of Physics, Faculty of Mathematics and Natural Sciences, University of Lampung, 2023)
Batteries are an important part of the power generation system, both solar power plants and motorized vehicle electrical systems. Battery capacity is something that must be considered for these various activities, because a decrease in battery capacity results in disruption of power distribution to users. The battery in this study is a battery or accumulator. The sample image is obtained using a thermal camera to determine the characteristics of the battery based on color. The basis for identifying characteristics is obtained by separating the RGB color components in the thermal image. Each color component will calculate the average pixel intensity value and see the difference in the resulting value. The results showed that the distinguishing characteristic between the sampling conditions was that the green pixel intensity mean value when the battery was being charged was higher than the condition of the battery before being charged and the condition of the battery when it was loaded. The average value when the battery is on the power side is 107 pixels green, while the average value when the battery is before charging is 81 pixels green and when the battery is loaded the average green value is 82 pixels.